A goal-oriented framework for analyzing and modeling city dashboards in smart cities. - Mannaro, Katiuscia; Baralla, Gavina; Garau, Chiara (Springer, 2018)
Das "City-Dashboard" ist eine interaktive Plattform, die Entscheidungsträgern und Bürgern kontinuierlich und in Echtzeit Informationen über die jeweilige Stadt bietet.

For several years, many cities around the world are moving through a number of initiatives to implement the so-called "city dashboards", as an opportunity for a new quality of urban life in terms of knowing and governing cities. The main contribution of this paper is to examine how city dashboards are performing on various metrics and comparing them in order to understand what they do. Starting from this perspective, to the best of our knowledge and by examining dashboard examples, there are many differences in the products that go by the name "city dashboards". Moreover there are several methodological and technical issues that are not dealt with and yet solved in terms of data, indicators and benchmarking. The design of a city dashboard needs a clear vision of the direction that public administrations intend to undertake, alongside an ability to build scenarios and analyze the results of experiments in the context of the changing urban variables. Given the gap in academic literature concerning this subject, we developed a goal-oriented framework for examining the characteristics of various city dashboards and developing a taxonomy. Our framework enables a more systematic process for developing an effective city dashboard and provides useful insights to decision makers. The results suggest that some features emerge and our findings highlight specific clusters.
Keywords: Smart City; E-Government; Urban Governance; Gemeindeverwaltung; Bürger; Interaktiv; Verwaltungsdaten; Informationstechnologie; Kommunikationstechnologie; Datenangebot; City Dashboard